2006
DOI: 10.1177/0739986306294255
|View full text |Cite
|
Sign up to set email alerts
|

Bicultural Social Development

Abstract: The conditions that result in bicultural social development among Latino children and adolescents represent the central focus of this article. The literature surrounding bicultural development is reviewed from four perspectives: (a) immigrant children and adolescents, (b) second generation Latinos or the offspring of immigrants, (c) later generation ethnic children and adolescents, and (d) mixed ethnic and racial heritage individuals. Each of these situations presents different socialization contexts and chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
178
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(184 citation statements)
references
References 40 publications
3
178
2
1
Order By: Relevance
“…Many Latino/a adolescent students find themselves needing to adapt to the mainstream culture while also maintaining ties with the culture of origin; this in turn may cause pressures to live by certain ethnic standards at home while also experiencing pressures to conform at school and in the broader community (Padilla, 2006). As it has been suggested that certain values may promote positive outcomes, it is important for cultural values to be studied when trying to understand a Mexican American college student's ability to be resilient.…”
mentioning
confidence: 99%
“…Many Latino/a adolescent students find themselves needing to adapt to the mainstream culture while also maintaining ties with the culture of origin; this in turn may cause pressures to live by certain ethnic standards at home while also experiencing pressures to conform at school and in the broader community (Padilla, 2006). As it has been suggested that certain values may promote positive outcomes, it is important for cultural values to be studied when trying to understand a Mexican American college student's ability to be resilient.…”
mentioning
confidence: 99%
“…In addition, the enculturation from the parent born outside the child's residence country is thought to be assisted by remote enculturation (Ferguson, Costigan, Clarke, & Ge, 2016). Children from such intermarriage parents are competent in both of their cultures (Padilla, 2006), develop a multi-ethnic identity (C. W. Stephan & Stephan, 1989) and their cultural values and attitudes lie between those of the immigrant culture and the native culture of the country of residence (Kalmijn, 2015;W. G. Stephan & Stephan, 1991).…”
Section: How Preschoolers React To Norm Violations Is Associated Withmentioning
confidence: 99%
“…Although few studies have examined differences across sub-groups, Cislo (2008) found Cubans young adults reported higher levels of ethnic identity than Nicaraguans (Cislo, 2008). As such, Study 2 predicted significant differences across site and nationality in recently While adolescents are exposed to American culture through participation in the school system (Padilla, 2006), as previously stated, adults settling in ethnically enclaves may not be inclined to adopt to the United States culture and/or identify as an American . That being said, research has emphasized the role adolescents, particularly immigrated adolescents, have in transmitting American values and culture (Padilla, 2006).…”
Section: Hypothesis 2b -Predictors Of Growth In Adolescents' and Theimentioning
confidence: 62%
“…As such, Study 2 predicted significant differences across site and nationality in recently While adolescents are exposed to American culture through participation in the school system (Padilla, 2006), as previously stated, adults settling in ethnically enclaves may not be inclined to adopt to the United States culture and/or identify as an American . That being said, research has emphasized the role adolescents, particularly immigrated adolescents, have in transmitting American values and culture (Padilla, 2006). As such, adolescents are likely encourage their caregivers' to explore the meaning of what being an American means to them.…”
Section: Hypothesis 2b -Predictors Of Growth In Adolescents' and Theimentioning
confidence: 62%